Pelatihan Aplikasi Komputer untuk Penulisan Ilmiah di SMPN 1 Pagerwojo Tulungagung Jawa Timur: Computer Application Training for Scientific Writing at SMPN 1 Pagerwojo Tulungagung East Java - Yamasari, Yuni; Qoiriah, Anita; Putra, Ricky Eka; Prihanto, Agus; Suartana, I Made; Prapanca, Aditya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Teacher professionalism development is one of the strategic steps in improving the quality of education at SMP Negeri 1 Pagerwojo, Tulungagung, East Java. However, limited access to training and a lack of utilization of technology are significant obstacles for teachers, especially in the field of scientific writing. Scientific writing skills are essential in improving teaching skills, developing learning materials, and contributing to educational literature. To solve this problem, this community service activity aims to enhance teachers' skills in scientific writing through training in the use of applications. The training utilizes key features, such as reference management, automatic citation settings, and scientific document management. The training method includes the application installation stage, direct training, and analysis of results through measuring participant responses using a Likert scale. The study showed that the training improved teachers' understanding and skills in utilizing technology to support scientific writing. Most participants responded positively to the training, with a percentage of 77.55%. These results indicate that similar training needs to be further developed to support teacher professionalism, especially in areas with limited access to training.